(untitled) (Malaysian Journal of Civil Engineering, 2021)
The construction sector is a significant contributor to the Gross Domestic Product of a developing country. Infrastructure improvement plays a vital role in this wherein highway construction is a dynamic sector requiring proper planning and scheduling multiple resources. Appropriate integration among various associated stakeholders is essential for a project’s success, aided by supply chain management. Resource planning is one of the basic concepts in supply chain management, with material and equipment management being the critical area. The main objective of this study is to develop a conceptual supply chain simulation model using ARENA, to analyze the equipment idling and utilization rate, keeping inter-arrival time for dispatch, the number of equipment, and working hours as constant. This model employs the real-time ‘best fit’ material utilization data as input. Material utilization data collected from 62 construction projects are analyzed to arrive at a ‘best fit’ probability distribution. This study’s conceptual supply chain simulation model helps formulate suitable material and equipment delivery plans to lessen risk in construction projects.